Análise de viabilidade de alternativas para transição energética e descarbonização em uma fábrica de chocolates - Gonçalves, Audrey Novelli (2024)
Decarbonization and energy transition are fundamental to combating climate change reducing greenhouse gas emissions and promoting the use of renewable sources of energy. These actions are essential to ensure a sustainable environment and mitigate the negative impacts of human activities on the global climate. In this sense, systems combining Heat Pump (HP), Organic Rankine Cycle (ORC), and Vapor Compression Refrigeration (VCR) have been proving to be a promising alternative to solve these issues and meet energy demands in the form of electrical energy, chilled water, and hot water. This study investigates the use of ORC-HP, ORC-VCR, and HP cycles in a chocolate factory, and the purpose is to aim for the generation of cold water to complement the refrigeration system, electricity for activation, and surplus energy. In addition to that, there is the production of hot water for the manufacturing process. From the defined nominal data, modeling thermodynamics is executed, resulting in mass and energy balances. Then, the economic analysis is based on a method of parametric equations for determining the costs of each piece of equipment to obtain the total value of the initial investment in each plant modeled. With these calculations, economic viability indicators are carried out: payback (simple and discounted), net present value (NPV), and internal rate of return (IRR) to assess whether investments are viable or not. The results show that, from the modeled cycles, only the heat pump system is economically viable. With an investment of R$ 13,076,507.47, the discounted payback is 2 years and 3 months, representing an IRR with a value of 51.40% p.a. The environmental analysis represents the lowest CO2 emission per ton, as the implementation of the project implies the elimination of natural gas, reducing the emission rate to 0.6018 tons of CO2 per hour. The results also demonstrate that the implementation of the ORC-HP system is not economically viable, as the total cost is strongly influenced by natural gas, nor environmentally advantageous due to high natural gas consumption, resulting in high CO2 emissions.